2019
DOI: 10.1186/s13063-019-3904-4
|View full text |Cite
|
Sign up to set email alerts
|

Landiolol, an ultra-short acting beta-1 blocker, for preventing postoperative lung cancer recurrence: study protocol for a phase III, multicenter randomized trial with two parallel groups of patients

Abstract: BackgroundRecurrence of cancer after curative surgery is a major problem after most cancer treatments. Increased sympathetic activity during the perioperative period could promote cancer cell invasion to blood vessels and angiogenesis, resulting in cancer metastasis. Recent studies showed that use of beta blockers can be associated with the prolonged survival of patients with cancer. The objective of this study is to evaluate the preventive effects of landiolol hydrochloride, which is an ultra-short-acting bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 195 The selective β1 blocker landiolol reduces lung cancer recurrence after operation. 196 Additionally, β-blockers positively affect cancer patients by reducing their intrusive thoughts. 197 Overall, the effects of β-blockers on TME and the whole organism indicate their potential application in future cancer treatments.…”
Section: Conventional Drugs With New Use: Candidate For Tme-targetingmentioning
confidence: 99%
“… 195 The selective β1 blocker landiolol reduces lung cancer recurrence after operation. 196 Additionally, β-blockers positively affect cancer patients by reducing their intrusive thoughts. 197 Overall, the effects of β-blockers on TME and the whole organism indicate their potential application in future cancer treatments.…”
Section: Conventional Drugs With New Use: Candidate For Tme-targetingmentioning
confidence: 99%
“…In a retrospective study with 77 patients of stage IIIa NSCLC treated with neoadjuvant chemoradiation and subsequent surgery, BB users were associated with a trend of improved OS at 1 year compared with the non-users in univariate analysis (p = 0.08) [ 39 ]. Another study with 57 lung cancer patients showed that perioperative intravenous administration of an ultra-short acting SBB landiolol prolonged relapse-free survival in these patients [ 40 ], and a phase III RCT has been started accordingly [ 41 ]. Results of future prospective studies and RCTs are expected to provide more reliable evidence regarding the association between BB use and OS in patients with lung cancer, preferably according in different histopathological type.…”
Section: Discussionmentioning
confidence: 99%
“…There are an increasing number of larger ongoing β-blocker RCTs aimed at assessing clinical cancer outcomes. 222 However, an obstacle to success in these studies is the limitation in recruitment due to competition with other traditional pharma-supported oncology trials that typically prohibit additional treatment with another agent such as propranolol. 214 , 223 As such, several attempts to test the impact of β-blockade in the context of cancer treatment have been terminated prematurely due to poor accrual (NCT02596867, NCT01857817, NCT03323710) or funding obstacles (NCT01988831).…”
Section: Pharmacologic Approaches To Reduce Stress-related Cancer Pro...mentioning
confidence: 99%